Transitional cell carcinoma of the bladder in young adult patients (Annals of Medical Research, 2021)
Aim: Transitional cell carcinoma of the bladder (TCC) mostly affects the middle and old population as in other cancers. We aimed to present the results and clinical behaviors of patients treated with bladder TCC under the age of 40 years.Material and Methods: Fifteen patients who were admitted to our clinic between 2005 and 2019 and diagnosed as TCC were evaluated retrospectively. Demographic characteristics, initial and follow-up transurethral resection pathologies, intravesical treatment and follow-up periods were evaluated. All patients underwent transurethral resection after ultrasonography (USG) and cystoscopy examination. Results: The most common complaint was macroscopic hematuria (n:12.80%).Smoking rate was 66% (n:10). The mean age of the patients was 32.4 (19-39). Male / female ratio was 13/2. The mean follow-up period was 55 weeks. Ten patients (66%) had single focus and five (34%) had multiple focus tumors. In 10 patients, the tumor pathology TaG1, TaG3 in 3, T1G1 in one and T1G3 in one patient were reported.4 patients received intravesical chemotherapy and four patients underwent intravesical immunotherapy (BCG). The recurrence rate was 53% (n:8) and the rate of pro- gression was 13% (n:2) (TaG1-T1G3). None of the patients progressed to T2 disease.Conclusuion: Bladder TCC under 40 years of age usually presents as TaG1. Survival rates are high if follow-up and treatment protocols are followed. It should be kept in mind that there may be bladder tumors in young adult patients regardless of age.Keywords: Bladder tumor; cystoscopy; hematuria.
Keywords: Bladder tumor; cystoscopy; hematuria.